Working from home - Behrens, Kristian,Kichko, Sergey,Thisse, Jacques-François (CESifo, Center for Economic Studies & Ifo Institute, 2021)
We develop a general equilibrium model with three primary production factors - land, skilled, and unskilled labor - and three sectors - construction, intermediate inputs, and final consumption - to study how different intensities of telecommuting affect the efficiency of firms that embrace home working, as well as its impact on the whole economy. In doing so, we pay particular attention to the effects of increasing working from home (WFH) that go through changes in the production and consumption of buildings: more WFH reduces firms' demands for office space, but increases workers' demand for living space since additional room is re-quired to work from home. We find that more WFH is a mixed blessing: the relationship between telecommuting and productivity or GDP is ∩-shaped, whereas telecommuting raises income inequality. Hence, WFH is not a panacea since an excessive downscaling of workspaces may be damaging to all and exacerbate economic inequality.
10419/232428
Keywords: Graue Literatur; working from home; alternative work arrangements; telecommuting; housing and office markets; land